Analytical modeling of degradation product partitioning kinetics in source zones containing entrapped DNAPL - Ramsburg, C. Andrew; Christ, John A.; Douglas, Scott R.; Boroumand, Ali (Tufts Archival Research Center, 2005)
Liquid-liquid equilibrium experiments indicate that there is a strong thermodynamic driving force for the reversible sequestration of cis-dichloroethene (DCE) within microbially active dense nonaqueous phase liquid (DNAPL) source zones containing chlorinated ethene solvents. Assessment of the importance of degradation product sequestration, however, requires accurate description of the mass transfer kinetics. Partitioning kinetics of cis-DCE were assessed in a series of transport experiments conducted in sandy columns containing uniformly entrapped tetrachloroethene (PCE)-nonaqueous phase liquids (NAPL). Effluent data from these experiments were simulated using an analytical solution adapted from the sorption literature. The solution permits interrogation of the relative importance of mass transfer resistance in the aqueous phase and NAPL. Column data and simulations suggest that the kinetic exchange of cis-DCE may be described with mass transfer correlations developed for the dissolution of pure component NAPLs. Diffusive transport within the entrapped ganglia was relatively fast, offering limited resistance to mass exchange. These results (1) establish the applicability of dissolution-based mass transfer correlations for modeling both absorption and dissolution of degradation products, (2) quantify the thermodynamic driving force for the partitioning of cis-DCE in PCE-NAPL by assessing the ternary phase behavior, and (3) guide incorporation and deployment of partitioning kinetics into multiphase compositional simulators when assessing or designing metabolic reductive dechlorination within DNAPL source zones. While focus is placed on examining degradation product partitioning in DNAPL source zones, results may also be useful when considering rate limitations in other liquid-liquid partitioning processes, such as partitioning tracer tests.